PENGARUH CAPITAL INTENSITY DAN INVENTORY INTENSITY TERHADAP AGRESIVITAS PAJAK YANG DIMODERASI OLEH GCG (GOOD CORPORATE GOVERNANCE) - Sitorus, Riris Rotua; Wibowo, Ari Tri (Media Akuntansi Perpajakan, 2018)
The purpose of this study was to determine the effect of Capital Intensity and Inventory Intensity on Tax Aggressiveness with GCG (Good Corporate Governance) as a moderating variable. This type of research is quantitative. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange in the 2015-2017 period consisting of 136 companies. The research sample consisted of 50 companies. The sampling technique with purposive sampling technique. The data used is secondary data on annual reports of manufacturing companies listed on the Indonesia Stock Exchange. Testing the hypothesis in this study using multiple linear regression analysis method with SPSS program.In this study using four variables, namely the independent variable is Capital Intensity as (X1) and Inventory Intensity (X2) on the dependent variable is Tax Aggressiveness (Y) with the moderating variable is Good Corporate Governance (Z). The results showed thatKeywords: Capital Intensity, Inventory Intensity, Tax Aggressivity